Merit and permission: gender, education and migration in western India. - Mathew, Leya (Journal of Ethnic & Migration Studies, 2025)
This paper presents a gendered infrastructural perspective on internal education migration in India. It demonstrates the power of merit to spur female agency, rekindle failed aspirations and establish migration flows despite family reluctance. The paper analyzes interviews conducted with 29 young women who had migrated locally to attend a premier pharmacy college. The young women were academic high achievers who had to move away from home to pursue desirable higher education. For most, families were hesitant to permit the move. The young women had to undertake interlinked gender work and academic work to achieve merit and permission for migration. Theoretically, the paper models the concept of migration infrastructure for internal education migration and further, analyzes how infrastructures are gendered. It describes how infrastructures of merit – including discourses, practices, institutions, regulations and networks that authoritatively sort students – also move them in varied but specific ways. While the state in India defines and regulates merit, it also discriminates in favor of the privileged and the disadvantaged and spatializes development. Alongside, families negotiate the risks associated with female academic mobility. To achieve migration, the young women had to navigate both.